2017
DOI: 10.1177/0022042617699196
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Treatment Clients’ Reactions to Graphic Warning Labels on Cigarette Packs

Abstract: Graphic warning labels (GWLs) on cigarette packs have been tested among diverse groups at high risk for tobacco use. However, little is known about the effectiveness of GWL interventions for persons with substance use disorders, whose smoking prevalence is 3 to 4 times that of the general population. After an experimental study which exposed clients in residential addiction treatment to GWLs for 30 days, we conducted five focus groups with trial participants (N = 33) to explore how exposure to the labels may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The image evoked memories and negative feelings, indicative of its personal relevance for some female respondents. 34 This finding, within a vulnerable, high-smoking group, corresponds with quantitative studies in the general population of smokers showing women’s heightened responses to images of babies relative to men’s responses. 2427…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…The image evoked memories and negative feelings, indicative of its personal relevance for some female respondents. 34 This finding, within a vulnerable, high-smoking group, corresponds with quantitative studies in the general population of smokers showing women’s heightened responses to images of babies relative to men’s responses. 2427…”
Section: Introductionsupporting
confidence: 72%
“…The present study found no differences between male and female smokers in SUD treatment in ratings of images of women and/or babies versus other images. The research on responses to images of babies on GWLs in general samples of smokers is mixed; some have not shown sex-based differences, 23 although others have shown women reporting personal relevance 34 and rating the images more strongly than men. 25,26,46 Numerous factors may contribute to different findings across studies, ranging from differences in participant samples (eg, smokers with SUDs vs. general smoking samples) to variations in methods (eg, ratings measures, types of analyses conducted, such as comparisons of difference scores as was done in our study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has some limitations. First, while GWLs have been shown to have differential effects on different subpopulations [ 11 , 18 , 37 ], our study could not confirm this argument by investigating the impact of GWLs on different subpopulations using the aggregate data at the national level. Second, smoking prevalence was measured as a single outcome variable.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, growing evidence demonstrates that GWLs are more effective in decreasing smoking than text-only warnings [ 4 , 9 , 10 , 11 , 12 ]. GWLs have been found to attract greater attention and greater recall of health warning messages among rural male smokeless tobacco users than text-based warnings [ 12 ].…”
Section: Introductionmentioning
confidence: 99%